REVITALISASI PENDIDIKAN ASWAJA AN NAHDLIYAH (KE-NU-AN) DALAM MENANGKAL FAHAM RADIKALISME DI SMK AL-AZHAR MENGANTI GRESIK - Arif, Muhamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The rise of radicalism ideology, became the main work of the madrasa as a guardian of Islamic ideology that rahmatan lil alamin.. A unique phenomenon was found by researchers in an educational institution, namely in the Al-Azhar Menganti Vocational School (SMK), a middle-level educational institution that is included in the shelter of the Darul Ihsan Menganti Islamic boarding school foundation. Al-Azhar Menganti Vocational School (SMK), at the beginning of the admission of new students, each new student was given material on religiousness (NU-an), and there was ta'lim muta'alim in the style of the cottage for Nahdlatul Ulama. In addition, the NU studies were a study that was the closing point at the end of each semester, as one of the objectives was to achieve Islam rahmatan lil alamin and efforts to win the rise of the radical movement. This study uses qualitative research methods that produce descriptive data in the form of written or oral words from people and behaviors that can be seen during the research process. Related to this is arranged on the background of this individual as a whole (intact) without any engineering. Some of the main capital invested in Al-Azhar Vocational School students, as a real effort to counteract the amount of radicalism in the world of education, one of which is by incorporating self-education into the school curriculum as a local substitute. In addition to the implementation sought by the al-Azhar Menganti Vocational School, it does not include several limitations in implementing Aswaja education (Ke-NU-An), which is translated, namely the number of books abroad Aswaja Nahdliyyin (Ke-NU-An), in the name of Aswaja (Ke-NU-An).Keywords: Education; Radicalism Ideology; Aswaja ideology